Scientific-Theoretical Foundations Of Studying Foreign Experience In Forming National And Universal Values Among Youth - Umarov Hamdam Tukhtaevich (Periodica Journal, 2025)
This article analyzes the phenomenological and axiological aspects of instilling national and universal values in youth in the context of transnational processes of social integration under globalization. Special attention is paid to the dialectical balance between universal cultural cohesion and the preservation of national identity. The article studies methodological mechanisms for shaping the younger generation on the basis of a system of axiological values through the experiences of Japan, Korea, China, and Finland. It also discusses ways to integrate national traditions and global values and their role in strengthening cultural competence among youth.
Keywords: Youth; national values; universal values; globalization